Comparison of the effects of simulated and actual short trail running tests on neuromuscular function in master trail runners - Panthong, S.; Thongsiri, N.; Suksom, D. (Journal of Physical Education and Sport, 2023)
Trail running is an increasingly popular endurance sport with races over variety of distances and terrains. Those prolonged running elicits decrease in muscle power output mediated by reductions in neuromuscular function. However, the evaluation of neuromuscular function is still limited in trail runners and difficult on the field setting.